Kajian Fatwa Dewan Syariah Nasional Tentang Mudharabah - Mursid, Fadhilah (TAWAZUN: Journal of Sharia Economic Law, 2020)
Until now, mudharabah is still carried out in people's lives even though it has been modified to a degree. Even in Islamic Financial Institutions, mudaraba becomes a mainstay product that is often offered by customers. With the increasing number of LKS that makes mudharabah as one of its flagship products. MUI as an institution that has the authority to issue fatwas related to Islamic economics through DSN considers it necessary to issue a fatwa on mudharabah so that the procedure is carried out in accordance with Islamic Sharia. Regarding the fatwa it is interesting to analyze how the implementation of the DSN fatwa on mudaraba in the study of muamalah fiqh. The researcher uses a descriptive qualitative research method which discusses comprehensively using various sources of primary and secondary literature data relating to the MUI DSN fatwas on mudharabah. The results of the study concluded that overall the existing fatwa was in accordance with the provisions contained in the treasury of Islamic economics. However, in carrying out legal construction as a legal standing, it is still very global, especially in the use of fiqh proposals. Even from a number of fatwas, there is a similar tendency in legal construction of different content of the fatwa.